It takes two to tango: Unlocking flood preparedness in Malaysia through social capital - Mohd Rozaimy, Ridzuan; Jamal Rizal, Razali; Noor Amira Syazwani, Abd Rahman (MNNF Publisher, 2023)
The increasing frequency and severity of floods around the world are straining social capital, as communities affected by these disasters often rely on their social networks and mutual support systems to cope with the aftermath and recovery efforts. Strong social capital can enhance resilience, facilitating cooperation and resource-sharing among affected individuals and communities during flood crises. However, the literature on the social capital-disaster preparedness nexus has not been holistically examined. Therefore, the purpose of the study is to reduce the gap by investigating the extent to which social capital was practiced in flood preparedness initiatives in Malaysia. This study employs a qualitative research approach using a library search method, focusing on peer-reviewed articles to examine the role of social capital in flood preparedness initiatives within the Malaysian context. The data for this analysis is drawn from published works, particularly journal articles relevant to the subject matter. The study's findings yielded mixed results regarding the extent of social capital's application in flood preparedness initiatives in Malaysia. In light of these findings, this study provides several recommendations to stakeholders to enhance the integration of social capital into future flood preparedness efforts and foster more effective community resilience.